As transformações da Universitas no mundo moderno - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This research was developed in the Graduate course in Education of the Universidade Estadual de Goiás, in the research line of Culture, School and Formation. It seeks to discuss the relations between organization, institution and the instrumentalized education in the University education, considering human formation. This way, it is considered important to reflect and comprehend the concepts, the origin and the manner how Universities and the teaching profession were thought, from the medieval times until modernity, influencing its fundamentals. It questions the conception of human formation of the University on the construction of intellectual autonomy of the students. It is a theoretical research of historical and philosophical character that is based on the bibliographical study of the theme. It seeks to demonstrate the transformations of the University education institutions, in organizations that prioritize the preparation to the labor market, mainly relegating the intellectual dimension and a humanized formation. Modernity, technical rationality and consumerism impact the education and penetrate the teaching profession and the educational formation that begin to attend, specially, the demands of labor market and the State. In this context, the University, in its majority, begins to operate as an organization, having as its motto the immediate results and of short term, leaving behind human formation. By showing itself in an institutionalized way, it becomes accessible only to a few, disregarding its social function, in which the access is universal. It intends to demonstrate that the University is an institution in which human formation is its goal and search, not only attending the labor technical excellence, but to what leads to intellectual autonomy.
The transformations of Universitas in the modern world
Keywords: Educação; Formação - Docência; Universidade; Reflexão; Education; Formation - Teaching; University; Reflection; CIENCIAS HUMANAS::EDUCACAO